Direct from solid natural products to pure compounds in a single step: Coupling online extraction with high‐speed counter‐current chromatography. Issue 18 (10th September 2018) - Guo, Keke; Peng, Mijun; Tong, Chaoying; Shi, Shuyun; Liu, Yuge
Abstract: Extraction is the most important step in the purification of bioactive compounds from natural products. This study introduces a simple online extraction strategy coupled with high‐speed counter‐current chromatography for efficient extraction and purification of bioactive components from solid natural products. For online extraction strategy, 1.0 g of ground Mangnolia officinalis or Piper nigrum was loaded into a guard column, which was then positioned on the manual injection valve instead of the sample loop. Bioactive components were directly extracted by the mobile phase of high‐speed counter‐current chromatography, and then transferred into high‐speed counter‐current chromatography for purification. In addition, the compatibility of the developed methodology for direct purification of bioactive components from fresh M. officinalis was successfully demonstrated. Obviously, in comparison with traditional offline heat‐reflux extraction, online extraction avoided the instrument, time, solvent, and energy consumption, and purified two phenolic compounds (honokiol and magnolol) from M. officinalis and three alkaloids (piperyline, piperine, and piperanine) from P. nigrum with high extraction efficiency. The superiority of the developed methodology is to establish an easy, rapid, and efficient technique for the purification of a wide variety of bioactive components from solid natural products.